2021
DOI: 10.3390/jcm10122729
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid as a Predictor for Early Allograft Dysfunction after Living Donor Liver Transplantation: A Prospective Observational Study

Abstract: Early allograft dysfunction (EAD) is a postoperative complication that may cause graft failure and mortality after liver transplantation. The objective of this study was to examine whether the preoperative serum uric acid (SUA) level may predict EAD. We performed a prospective observational study, including 61 donor/recipient pairs who underwent living donor liver transplantation (LDLT). In the univariate and multivariate analysis, SUA ≤4.4 mg/dL was related to a five-fold (odds ratio (OR): 5.16, 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Other biomarkers such as inflammatory cytokines, chemokines, metabolites, lipid profile, and factor V had also proved to be associated with EAD. 8,17,18,[20][21][22][23]25 However, the QOE supporting their utility is relatively low due to single study and small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Other biomarkers such as inflammatory cytokines, chemokines, metabolites, lipid profile, and factor V had also proved to be associated with EAD. 8,17,18,[20][21][22][23]25 However, the QOE supporting their utility is relatively low due to single study and small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…A number of risk factors for the incidence of EAD have been identified by previous studies including recipient-related, donor-related, and surgical factors ( 7 , 9 , 23 ). Golse et al reported the potentially predictive utility of lactate for EAD.…”
Section: Discussionmentioning
confidence: 99%
“…There are many mechanisms of EAD, among which ischemia-reperfusion injury (IRI) remains the most likely ( 6 ). There are also many risk factors for the incidence of EAD, such as donor body mass index (BMI), uric acid, postoperative hepatic artery resistance index, and the C-reactive protein-to-albumin ratio, which have been reported in previous studies ( 5 , 7 9 ).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, NLR, when combined with AFP, CEA and uric acid, gave an AUROC as high as 0.933. Uric acid has recently been identified as a predictor for liver function after living donor liver transplantation [36]. Uric acid has been known for its antioxidant activity in various diseases and the liver is the major site of uric acid production.…”
Section: Discussionmentioning
confidence: 99%